(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Polymer brushes are assemblies of macromolecules that are tethered by one end to a surface or interface. The advantage of polymer brushes over other surface modification methods (e.g. selfassembled monolayers) is their mechanical and chemical robustness, coupled with a high degree of synthetic flexibility towards the introduction of a variety of functional groups. In this paper, an overview of the representative synthesis method of polymer brushes is presented and their potential applications on smart surfaces, wettability and biocompatible surfaces are explored. Their potential applications in textile engineering are discussed.